New suitable deprotonating matrices for the analysis of carboxylic acids and some acidic compounds by matrix‐assisted laser desorption/ionization mass spectrometry in negative ion mode. (24th November 2020) - Krivosheina, Mariya S.; Borisov, Roman S.; Zhilyaev, Dmitry I.; Matveeva, Mariya D.; Zaikin, Vladimir G.
Abstract : Rationale: Direct non‐derivatization analysis of organic acids and acidic compounds by matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry (MS) in positive ion mode is not always possible due to the low ionization efficiency of analytes. Some new efficient deprotonating matrices were suggested that allowed the production of negative ions from acidic compounds during MALDI‐MS experiments. Methods: Various tested carboxyl‐containing compounds as well as compounds with acidic properties were mixed with the suggested deprotonating matrices [4‐dimethylaminobenzaldehyde (DMABA), N, N ‐dimethylamino‐ p ‐phenylenediamine or 3‐aminoquinoline] and applied on a standard MALDI target followed by recording MALDI mass spectra in negative ion mode. Results: All the tested acidic compounds mixed with the suggested deprotonating matrices produced abundant [M − H] − ions under MALDI conditions. DMABA produced the strongest signals reflecting greater sensitivity of analysis. Conclusions: The suggested deprotonating matrices are commercially available compounds and are good alternatives to well‐known matrices of this kind and, in particular, the often used 9‐aminoacridine. DMABA is the best of the tested potential matrices and is suitable for the detection of low molecular weight carboxyl‐containing compounds, substituted phenols, and mixtures of naphthenic acids by (−)MALDI‐MS.